235 TRIBBLES-1 CONTRIBUTES TO MONOCYTE MIGRATION IN EXPERIMENTAL PERITONITIS. (24th May 2013) - Angyal, A; Daigneault, M; Hadadi, E; Ariaans, M; Burnett, A; Wilson, H; Ridger, V; Kiss-Toth, E
Abstract : Introduction: Mitogen activated protein kinase (MAPK) cascades are involved in the regulation of several cellular responses including migration or proliferation. We have shown previously that tribbles-1 (trb-1), a member of the tribbles family of adaptor/scaffold proteins controls vascular smooth muscle proliferation and chemotaxis via a direct interaction with the JNK activator kinase, MKK4. However, a regulatory role in monocyte/macrophage function for members of the tribbles family has also been reported. With the current work, we aimed to gain a better understanding of the early steps of monocyte recruitment under inflammatory conditions, and in particular, the contribution of tribbles-1 to these processes. Methods: We induced experimental peritonitis in trb-1 KO and trb-1 transgenic mice, where the expression of this gene was specifically modulated in the monocyte/macrophage lineage, and their littermate controls by injecting 1ml 4% thioglycollate to the peritoneal cavity. The composition of the cells infiltrating the peritoneum was analysed at 0, 6 and 24 hours post-injection by multi-colour flow cytometry. We also measured the cytokine content of the lavage fluids via the BD TM Cytometric Bead Array (CBA). Results: At 6 and 24 hours post-injection we found a significant increase in the infiltration of monocytes to the peritoneal cavity in trb-1 KO animals compared to littermate controls, while the trb-1 over-expressing monocytes refrained from entering the peritoneum. We quantified the amount of IL-1a/b, TNFa, MIP1a/b and KC in the samples and found no significant difference in the production of any of these cytokines. Conclusions: Trb-1 is involved in the regulation of monocyte migration under inflammatory conditions and therefore may play a significant role in the early steps of monocyte recruitment. Via this mechanism, trb-1 may contribute to the development of chronic inflammation and atherosclerosis. Further investigations will determine whether differences in the expression of leukocyte cell adhesion molecules (CAM) or other signalling abnormalities are responsible for the altered migration pattern of trb-1 KO and trb-1 transgenic monocytes.